Dielectric Formulation of the Nuclear Many-Body Problem - Mitran, Ovidiu (My University, 1971)
It is known in the case of an electron gas that the Coulomb force between electrons is screened due to the density variation around the electrons. In a similar way the force acting between nucleons in nuclear matter may be appreciably different from the free nucleon-nucleon interactions. The main theme of this thesis is to examine the "Screening" effect of the nuclear force. To this end, first the dielectric formulation of the theory of an electron gas is reviewed. Relationship among the chain-diagram approximation, the random phase approximation and the dieledtric formulation is discussed in detail. These techniques are then applied to nuclear matter taking the one-pion exchange potential as an example. It is found that the screening effect on the nuclear force in nuclear matter is indeed quite appreciable. The validity of the approximations is discussed.
Keywords: Dielectric Formulation; Nuclear; Many-Body Problem; electron gas